Nasopharyngeal carriage and risk factors of major meningitis pathogens among asymptomatic healthcare workers in paediatric units in Benin, with serogroup distribution of Neisseria meningitidis - Chakir Ishola Bello; Cyriaque Comlan Degbey; Yves Eric Denon; Sessi Armel R. Hinvi; Lamine Baba-Moussa (BMC Infectious Diseases)
Abstract Background Healthcare workers in paediatric settings are in close contact with vulnerable children and may serve as reservoirs and vectors for the transmission of respiratory pathogens such as Streptococcus pneumoniae, Neisseria meningitidis, and Haemophilus influenzae. In the African meningitis belt, data on asymptomatic carriage of these pathogens among healthcare workers remain scarce. This study aimed to assess the nasopharyngeal carriage of these three major meningitis-associated bacteria among paediatric healthcare personnel in Benin. Methods A cross-sectional study was conducted from September 2023 to December 2024 among 221 healthcare workers working in paediatric and neonatology units. Nasopharyngeal swabs were collected and analysed using quantitative real-time Polymerase Chain Reaction to detect S. pneumoniae (lytA), N. meningitidis (sodC), and H. influenzae (hpd3), as well as to characterise N. meningitidis serogroups and detect H. influenzae type b. Sociodemographic and clinical data were collected through a structured questionnaire. Associations between participant characteristics and pathogen carriage were assessed using chi-square tests and binary logistic regression, with a significance threshold set at p < 0.05. Results The nasopharyngeal carriage prevalence was 24.4% (54/221) for S. pneumoniae, 11.8% (26/221) for H. influenzae, and 10.0% (22/221) for N. meningitidis. Among the meningococcal carriers, 8 (36.4%) carried serogroup Y, 3 (13.6%) serogroup X, and 1 (4.5%) serogroup A. The remaining positive samples did not belong to any of the major vaccine-targeted serogroups (A, B, C, W, X, Y). None of the Haemophilus influenzae-positive samples were of serotype b. Pneumococcal carriage was significantly associated with younger age (18–35 years), and residence within the meningitis belt (p < 0.05). Similarly, Neisseria meningitidis carriage showed a significant association with residence in the meningitis belt. In contrast, no significant association was observed between Haemophilus influenzae carriage and any of the variables assessed. Conclusion Our findings reveal a substantial carriage of meningitis-related pathogens among paediatric healthcare workers, notably Streptococcus pneumoniae, Haemophilus influenzae and Neisseria meningitidis. The predominance of non-vaccine N. meningitidis serogroups (Y and X) and the absence of H. influenzae b suggest the need for expanded molecular surveillance and reconsideration of vaccine strategies targeting healthcare workers. These results emphasize the importance of infection prevention and control measures measures in paediatric care settings.